Nutrition Education for Babies and Toddlers - Marsanti, Avicena Sakufa; Handayani, Prita; Yuniana, Amama; Seka, Arum; Anindita, Dhea; Afrida, Diza; Alfi, Fahida; Anuraga, Gita (Jurnal Pengabdian Masyarakat, 2024)
Purpose: Providing education to the community so that partner communities have the ability and success in implementing efforts and actions to prevent malnutrition in Balerejo Village, Kawedanan District, Magetan Regency. Method: The method of this activity is providing education and motivation with the theme "Education about Balanced Nutrition for Babies/Toddlers in Balerejo Village, Kawedanan District, Magetan Regency". This community service uses lecture and leaflet methods. Practical Applications: With this balanced nutrition education, it is hoped that mothers of babies and toddlers in Balerejo village will know about fulfilling balanced nutrition for babies and toddlers and the concept of balanced nutrition in "fill my plate" to prevent malnutrition in babies and toddlers. It is also hoped that mothers of babies and toddlers can be motivated to continue monitoring and providing balanced nutrition for their babies and toddlers. Conclusion: The results of the program that has been implemented are that the majority of people in Balerejo Village understand and understand the problem of malnutrition in babies and toddlers, starting from counseling and education on balanced nutrition for mothers of babies and toddlers. And the impact that will occur on the community in the future after the program is implemented can increase the interest of the elderly community in Balerejo Village to carry out early detection and prevention of malnutrition problems in babies and toddlers. Apart from that, the program that has been implemented has become a good habit in the community, so that it can improve health status.